Uniqueness of limit cycle in the predator-prey system with symmetric prey isocline - Hasík, K (Mathematical biosciences, 2000)
We consider a special form of the Gause model of interactions between predator and prey populations. Using the ideas of Cheng, we prove the uniqueness of the limit cycle for more general systems, satisfying some additional conditions. These include also a condition due to Kuang and Freedman. Moreover, in this paper it is shown that the similar generalization of Cheng's uniqueness proof by Conway and Smoller is not correct.
Keywords: biologické modely; Models, Biological; predátorské chování; Predatory Behavior; zvířata; hustota populace; Population Density; Animals